2017
DOI: 10.18061/1811/81073
|View full text |Cite
|
Sign up to set email alerts
|

Reviving the Demographic Study of the Amish

Abstract: The Amish exhibit distinctive demographic patterns, notably high fertility. While scholars have studied Amish population dynamics for more than a half century, recent research in this area is limited. We believe the time is ripe to reverse this trend. This article reviews data collection methods, points to a variety of accessible sources of new data, presents some preliminary results from the analysis of one such source (the McKune dataset for Holmes County, Ohio), introduces the research agenda and work of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…The Amish are a culturally isolated population with extensive genealogical records dating back to their emigration to North America [ 49 ]. Community-based directories and research-based resources, described elsewhere, have been developed to curate these data [ 50 ]. To determine the relatedness of the GGLEAM study participants, we queried the Anabaptist Genealogy Database (AGDB) [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Amish are a culturally isolated population with extensive genealogical records dating back to their emigration to North America [ 49 ]. Community-based directories and research-based resources, described elsewhere, have been developed to curate these data [ 50 ]. To determine the relatedness of the GGLEAM study participants, we queried the Anabaptist Genealogy Database (AGDB) [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…While the average number of children for non-Amish families in the United States is approximately two children (U.S. Census Bureau, n.d.), Kraybill et al (2013) indicate the average number of children for Amish families is seven (Ericksen et al, 1979). In a study of Holmes County Amish, Colyer et al (2017) report the median number of children remained constant at six from 1965 to 1996 and then declined to five children in 2000 and 2005 with a further decline to four children in 2010. Of note, abortions are not permitted within the Amish belief system (Kraybill et al, 2013).…”
Section: Current Researchmentioning
confidence: 99%
“…The North American Amish, an ethnically Swiss-German population in the Anabaptist Christian religious tradition (Anderson 2020), represent a conspicuous exception to the West's demographic transition. While Amish mortality rates dropped in tandem with those of North America's populations throughout the twentieth century (Smith 1960;Hewner 1998;Mitchell et al 2001), studies have consistently reported completed fertility of anywhere between six and eight children per Amish woman (Colyer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Directory is an unrivalled source of demographic data about the Amish. Representatives from each church submit updated information to the publisher, and the directory includes household members' names and immediate relations; birth, death, marriage, and remarriage dates; street addresses; and select social variables including the household head's occupation and ministerial status (Colyer et al 2017). (Remarriage is permissible only if a spouse dies; divorce is forbidden, although separation is occasionally tolerated.)…”
Section: Introductionmentioning
confidence: 99%